Precision Medicine - Cascorbi, Ingolf; Schwab, Matthias (Cham : Springer International Publishing : Imprint: Springer, 2023)
The rapidly increased understanding of the molecular background of complex diseases facilitated the development of highly advanced therapeutic concepts. Such concepts aiming to consider individual signatures of genomic and proteomic biomarkers including pharmacogenomics as well as advanced diagnostic tools have been successfully implemented in clinical practice in various fields leading to significant improvement of treatment successes. This volume gives an up-to-date overview on applications of precision medicine in various clinical entities, on advanced techniques as well as on economic considerations.
Part 1. Pharmacogenomics -- Building evidence in RCTs Implementation of pharmacogenomics in healthcare in the UK -- Part 2. Precision medicine in clinical entities -- Precision medicine in therapy of non-solid cancer -- Molecular Mechanisms of Tyrosine Kinase Inhibitor Resistance in Chronic Myeloid Leukemia -- Precision medicine in Asthma -- Precision medicine in Diabetes -- Precision Medicine in Antidepressants Treatment -- Precision Medicine in Neuropathic Pain -- Part 3. Techniques in Precision Medicine -- Imaging techniques in pharmacological precision medicine -- Challenges to use NGS data to optimize drug therapy -- Part 4. Economics -- Pharmacoeconomics in precision medicine. .
Keywords: Pharmacology; Internal medicine; Cancer; Pharmacology; Internal Medicine; Cancer Biology